2013
DOI: 10.1111/anu.12046
|View full text |Cite
|
Sign up to set email alerts
|

Seven fish oil substitutes over a rainbow trout grow-out cycle: I) Effects on performance and fatty acid metabolism

Abstract: A long-term feeding trial was implemented on rainbow trout (Oncorhynchus mykiss) to assess the effects of seven alternative oils on fish performance and fatty acid metabolism. The tested oils were as follows: monola (a high oleic acid canola cultivar; MO), canola (rapeseed; CO), poultry by-product (chicken fat; PbPO), palm (PO), sunflower (SFO), high oleic acid sunflower (HOSFO) and soybean (SBO). All tested oils were included at a 75% substitution level of fish oil (FO) and were compared with a control diet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 42 publications
3
31
2
1
Order By: Relevance
“…Furthermore, EPA levels were increased in the livers of AV‐fed fish. This is in contrast to the findings of many studies, showing that the substitution of fish oil by vegetable oils decreases the EPA and DHA tissue levels in salmonids (Bell et al, , ; Turchini et al, ).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Furthermore, EPA levels were increased in the livers of AV‐fed fish. This is in contrast to the findings of many studies, showing that the substitution of fish oil by vegetable oils decreases the EPA and DHA tissue levels in salmonids (Bell et al, , ; Turchini et al, ).…”
Section: Discussioncontrasting
confidence: 95%
“…AV-diets include a blend of Ahiflower oil (3.8% of DM) and other vegetable oils (7.7% of DM). C, EQ1, EQ2, and EQ3 indicate the supplementation of the AV-diets with 0.0%, 0.1%, 0.2%, and 0.3% of DM of equol Initial FV AV-C AV-EQ1 AV-EQ2 AV-EQ3 substitution of fish oil by vegetable oils decreases the EPA and DHA tissue levels in salmonids (Bell et al, , 2003Turchini et al, 2013). Specifically, the EPA and DHA liver levels were affected by the dietary treatments.…”
Section: Effects On Lc-pufa Tissue Levelsmentioning
confidence: 99%
“…For example, the LC-PUFA sparing effect of feeding C 18 PUFA-poor lipids was reportedly marginal in Nile Tilapia Oreochromis niloticus Mulligan and Trushenski 2013), and Turchini et al (2013b) reported no difference between C 18 PUFA-rich canola and MUFA-rich "monola" oil (18:1[n-9]-rich canola cultivar) in terms of their effects on fillet fatty acid profile in Rainbow Trout. Similarly, a range of MUFA-rich lipids offered no advantage over C 18 PUFA-rich soybean oil in conserving whole-body LC-PUFA content in Rainbow Trout (Turchini et al 2013a), and Atlantic Salmon Salmo salar fed 18:1(n-9)-rich sunflower oil Downloaded by [University of Nebraska, Lincoln] at 17:52 11 April 2015 retained as much LC-PUFAs in the white muscle as those fed less MUFA-rich palm oil (Torstensen et al 2000). Our cross-study comparison of D jh values in hybrid Striped Bass reveals that at least some attempts to spare fish oil with SFA-and MUFA-rich lipids, such as coconut oil, palm oil, poultry fat, and nonhydrogenated MUFA-enriched soybean oil, have resulted in profiles ranking above the 50th percentile for profile distortion ( Figure 1; Trushenski 2009;Trushenski and Kohler 2011;Crouse et al 2013; the present experiment).…”
Section: Discussionmentioning
confidence: 99%
“…The fillet n-3 PUFA content, however, can be affected (Caballero et al 2002;Turchini et al (2013a), and thus, the fillet quality that is of importance to consumers can be altered (Turchini et al 2013b). For this reason, total replacement of fish oil with vegetable oil for many species, including rainbow trout, is still considered impossible due to the resultant modification of the fatty acid composition of cultured fish.…”
Section: Aquaculture Nutritionmentioning
confidence: 99%
“…Studies in gilthead seabream (Benedito-Palos et al 2008), pikeperch (Kowalska et al 2011) and Atlantic salmon (Bell et al 2003;Torstensen et al 2004) reported similar disorders of lipid metabolism and alterations in fatty acid profiles of the fillets when diets containing fish oil-alternative dietary lipid sources were fed. Studies examining replacement of fish oil in diets of rainbow trout have not always observed reduced growth but have documented altered liver fatty acid metabolism and muscle n-3 PUFA content (Caballero et al 2002;Turchini et al 2013a). Consequently, the fillet was deemed less acceptable by consumers due to inability to supply substantial amounts of long-chain n-3 PUFA (Caballero et al 2002;Turchini et al 2013b).…”
mentioning
confidence: 99%